Rising Protectionism within the Global Economy - Gabriela Prelipcean; Diana Georgiana Bucătar (Ovidius University Annals: Economic Sciences Series, 2019)
After more than two centuries during which economists have pointed to the benefits of free trade, compared to the costs of applying trade restrictions, one of the most significant events marking the beginning of the 21st century is the transition from globalization and trade integration to nationalism and protectionism. The International Monetary Fund warns that protectionism is increasing and poses a threat to global economic growth. Uncertainty related to protectionism is pressing for the economic outlook situation and could erode and further affect the euro area and the global economy. The present article discusses why rising protectionism re-emerged in the global economic arena, identifies a set of economic and socio-political determinants and brings to the forefront possible macroeconomic implications of an escalation in trade tensions. We propose to tackle current movements such as Brexit and Euroskepticism that challenge the principles of trade liberalization, generating an increase in sovereign national accents.